Effect of surfactants and grafted copolymer on stability of bentonite particles dispersion in brine system - Ahmed, A.A. (Asian Research Publishing Network, 2016)
A major issue for the oil and gas industry is the production of high water from many fields due to massive water injection. Reducing the water production while improving oil recovery from these fields is a key challenge. Polymer gel has been widely used to shut offwater-producing zones, but it is not suitable for high temperature reservoirs (> 100 Â°C). Recently, developing a thermally stable plugging agent has posed a challenge for oil and gas business. The aims of the present study are to investigate the stability and aggregation rates of 0.1 w/w bentonite particles dispersion in the brine system (1 w/w NaCl) at various conditions. The main objective is to select an effective and suitable method for stabilizing of bentonite colloids for possible propagation in porous media to plug high permeable zones (thief zones). The effects of surfactants (cationic/anionic), and grafted poly(N-isopropyl acrylamide-co-acrylic Acid) on the bentonite colloids aggregation kinetics and stabilities were investigated. In this study, a series of bentonite dispersions stability tests were conducted using light transmission and backscattering measurements by Turbiscan. Time evolution of turbidity was employed to define colloids aggregation rates. The study revealed that surfactants and polymer grafted bentonite had significant impacts on the stability of bentonite particles dispersion. It was observed that anionic surfactant (SDS) has more tendency to stabilize the particles compared to cationic surfactant. However, both surfactants have shown unstable dispersion in 1 NaCl. Also, increasing SDS surfactant concentration decreases aggregation and migration rates, whereas cationic surfactant (DTAB) exhibits an opposite phenomenon. It was also observed from the Turbiscan measurements that the aggregation and sedimentation dynamics fell into two patterns, slow and rapid coagulations. Under studied conditions, grafted bentonite effectively showed excellent dispersion stability. Â© 2006-2016 Asian Research Publishing Network (ARPN).